Starting and Subsequent Earnings of Young Workers in Different Sized Firms - Tannen, Michael (Archives of Business Research, 2022)
Based upon the highly innovative Project TALENT Longitudinal Database, this study tracks the starting earnings and subsequent early earnings growth of young males who began their work careers at either a smaller (<100 employees) or larger private firm more than a generation ago. Prior evidence based upon less rich databases found that earnings were systematically higher in larger firms but did not have access to many other variables that could affect projected earnings which are available in the TALENT database. Earnings regressions are estimated here including not only usual explanatory variables of years of schooling and labor market experience, but also adding other variables pertaining to prior job experience, military service, IQ, socioeconomic background and some other factors. The findings indicate that while starting earnings of those in this database were indeed higher in larger firms, the gap evaporated fairly quickly with projected earnings of those in smaller firms featuring a small earnings premium. The results here suggest guidance based upon the body of prior evidence may have been less reliable than thought, and that evidence itself may not provide as useful a baseline as desired for subsequent research addressing whether this pattern continues for recent cohorts.